2016
DOI: 10.1177/1049909115603960
|View full text |Cite
|
Sign up to set email alerts
|

A Formal Palliative Care Service Improves the Quality of Care in Patients with Stage IV Cancer and Bowel Obstruction

Abstract: Palliative care consultation improves the quality of care for patients with stage IV cancer and bowel obstruction, with particular benefits in symptom management, end-of-life discussion, and disposition to hospice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Wiesenthal et al (2017) found that the patients who received the outpatient consultation services had more designation rates of DNR order than the patients who received inpatient consultation services and the patients who did not receive any consultation service within the 6 months before their final admission to the hospital (22% under outpatients consultation, 8% under inpatients consultation; p = 0.002). Gabriel et al (2017) also showed that among the 38 patients with the stage IV colorectal and gynecologic cancers, those who received the palliative care service consultation had more DNR designations (57.9%) than the patients who received the usual care (10.5%) ( p = 0.002). Similarly, Huang et al (2017) found that compared with the control group (37%), the patients in the hospice-share care model group had higher DNR designation rates (95%) ( p < 0.001).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Wiesenthal et al (2017) found that the patients who received the outpatient consultation services had more designation rates of DNR order than the patients who received inpatient consultation services and the patients who did not receive any consultation service within the 6 months before their final admission to the hospital (22% under outpatients consultation, 8% under inpatients consultation; p = 0.002). Gabriel et al (2017) also showed that among the 38 patients with the stage IV colorectal and gynecologic cancers, those who received the palliative care service consultation had more DNR designations (57.9%) than the patients who received the usual care (10.5%) ( p = 0.002). Similarly, Huang et al (2017) found that compared with the control group (37%), the patients in the hospice-share care model group had higher DNR designation rates (95%) ( p < 0.001).…”
Section: Resultsmentioning
confidence: 98%
“…Table 2 describes the characteristics of the fourteen included studies. They were published between 2007 and 2017 in five countries: Hong Kong, China (Tse et al, 2007), Japan (Sato et al, 2008), United States (Bell et al, 2011; Delgado-Guay et al, 2009; Gabriel et al, 2017; Peltier et al, 2017; Rhondali et al, 2013; Shuman et al, 2013; Wiesenthal et al, 2017), Australia (Stein et al, 2013), and Taiwan (Huang et al, 2017; Kao et al, 2014; Loke et al, 2011; Wu et al, 2016). Of the 14 studies, two adopted randomized controlled trail designs and 12 used retrospective chart review designs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations